Promoting users' intention to share online health articles on social media: The role of confirmation bias. Issue 6 (November 2020) - Zhao, Haiping; Fu, Shaoxiong; Chen, Xiaoyu
Highlights: Users with a high level of eHealth literacy are more likely to share positive health articles when they have extreme confirmation bias. Users with a high level of eHealth literacy are more likely to share negative health articles when they have moderate confirmation bias or no confirmation bias. Users with a low level of eHealth literacy are more likely to share health articles regardless of positive or negative content valence when they have moderate positive confirmation bias. Abstract: Nowadays, it is a common practice for healthcare professionals to spread medical knowledge by posting health articles on social media. However, promoting users' intention to share such articles is challenging because the extent of sharing intention varies in their eHealth literacy (high or low) and the content valence of the article that they are exposed to (positive or negative). This study investigates boundary conditions under which eHealth literacy and content valence help to increase users' intention to share by introducing a moderating role of confirmation bias—a tendency to prefer information that conforms to their initial beliefs. A 2 (eHealth literacy: high vs. low) × 2 (content valence: positive vs. negative) between-subjects experiment was conducted in a sample of 80 participants. Levels of confirmation bias ranging from extreme negative bias to extreme positive bias among the participants were assessed during the experiment. Results suggested that: (1) users with a high level of eHealth literacy were more likely to share positive health articles when they had extreme confirmation bias; (2) users with a high level of eHealth literacy were more likely to share negative health articles when they had moderate confirmation bias or no confirmation bias; (3) users with a low level of eHealth literacy were more likely to share health articles regardless of positive or negative content valence when they had moderate positive confirmation bias. This study sheds new light on the role of confirmation bias in users' health information sharing. Also, it offers implications for health information providers who want to increase the visibility of their online health articles: they need to consider readers' eHealth literacy and confirmation bias when deciding the content valence of the articles.